PENERAPAN PSAK 71 PADA RASIO KEUANGAN DI PERUSAHAAN TELEKOMUNIKASI - Wiyarti, Evy Steelyana; Prameswari, Ayundita (Unitri Press, 2024)
The implementation of PSAK 71 at PT. Centratama Telekomunikasi Indonesia Tbk focuses on financial instruments, resulting in changes to accounts receivable and cash equivalents. The adoption of PSAK 71 aims to enhance the quality of financial reporting by regulating classification and measurement, impairment, and hedge accounting. Moreover, the transition from PSAK 55 to PSAK 71 aims to simplify the impairment model. The impairment method in PSAK 71, namely Expected Credit Loss, allows for the recognition of credit losses before they occur, differing from the Loss Incurred Method in PSAK 55.This research aims to evaluate the financial performance and factors that changed after the implementation of PSAK 71 at PT. Centratama Telekomunikasi Indonesia Tbk. Data analysis employs qualitative descriptive and comparative techniques on financial ratios. The study reveals fluctuations in ratio values, with a decrease in liquidity and an increase in activity, solvency, and profitability. The conclusion emphasizes the improvement in the quality of financial reporting post-implementation of PSAK 71, despite some changes in ratios. The significant implications of this research highlight the positive impact of implementing PSAK 71 on the company's financial management.